2022
DOI: 10.1007/s10072-022-06104-w
|View full text |Cite|
|
Sign up to set email alerts
|

The Italian tremor Network (TITAN): rationale, design and preliminary findings

Abstract: Introduction The recently released classification has revised the nosology of tremor, defining essential tremor (ET) as a syndrome and fueling an enlightened debate about some newly conceptualized entities such as ET-plus. As a result, precise information of demographics, clinical features, and about the natural history of these conditions are lacking. Methods The ITAlian tremor Network (TITAN) is a multicenter data collection platform, the aim of which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 33 publications
2
31
1
Order By: Relevance
“…We also found that anxiety and depression were more common in ET than in normal subjects, in line with previous evidence [3]. Finally, consistent with previous data, 80% of patients presented soft signs [1], including rest tremor, subtle bradykinesia and dystonia [33], impaired tandem gait, and MCI, and thus could be categorized as ET‐plus [29, 34–36]. At follow‐up evaluation, we found that tremor severity in ET increased, with tremor spread in different body segments and a worsening of tremor during specific complex tasks (i.e., drawing spirals and several activities of daily living).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that anxiety and depression were more common in ET than in normal subjects, in line with previous evidence [3]. Finally, consistent with previous data, 80% of patients presented soft signs [1], including rest tremor, subtle bradykinesia and dystonia [33], impaired tandem gait, and MCI, and thus could be categorized as ET‐plus [29, 34–36]. At follow‐up evaluation, we found that tremor severity in ET increased, with tremor spread in different body segments and a worsening of tremor during specific complex tasks (i.e., drawing spirals and several activities of daily living).…”
Section: Discussionsupporting
confidence: 90%
“…By definition, all patients presented upper limb postural and/or kinetic tremor, but a considerable proportion also had tremor in other body segments, with the head being the most involved segment [ 5 , 18 ]. More than half of patients had a family history of tremor [ 29 ]. Cognitive and psychiatric disorders were also observed, confirming a higher prevalence of MCI in ET than in the general population [ 30 ], with executive function and memory being the most involved domains [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some previous studies retrospectively reclassified ET patients evaluated before 2018, which were prone to recall bias [11][12][13][14]. Several ET cohorts with relatively small sample sizes were prospectively enrolled, most of which were conducted in a single center [5,[15][16][17][18][19][20]. The Italian tremor network (TITAN) prospectively assessesed the phenomenology and natural history of different tremor syndromes based on the new classification in Italy [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several ET cohorts with relatively small sample sizes were prospectively enrolled, most of which were conducted in a single center [5,[15][16][17][18][19][20]. The Italian tremor network (TITAN) prospectively assessesed the phenomenology and natural history of different tremor syndromes based on the new classification in Italy [20]. To further study the clinical heterogeneity of ET according to the new consensus statement, determine the proportion of ET plus in mainland China, recognize the deviations from ET, evaluate the non-motor symptoms in patients with ET, and explore the possible factors related to ET plus, the China Essential Tremor Alliance launched a large multicenter registry study of ET named the National Survey of Essential Tremor Plus in China (NSETP-China).…”
Section: Introductionmentioning
confidence: 99%
“…scored both p-spirals and d-spirals of 11 patients with the most common action tremor syndromes, including ET, ET-plus, and dystonic tremor. 3 Using the Spearman test, a significant, strong correlation was found between p-spiral and d-spiral scores (ρ = 0.772, P < 0.001; Fig. 1A).…”
mentioning
confidence: 89%